Impedance cure and flow monitoring in the processing of advanced composites. - Skordos, Alexandros A.; Partridge, Ivana K. (Cranfield University, 2001)
The paper presents recent developments in the area of impedance cure and flow monitoring of thermosetting matrix/continuous reinforcement composites. Impedance cure monitoring is a variation of dielectric cure monitoring which follows the progress of the curing reaction and the accompanying structural phenomena by means of the impedance spectrum response of the curing material. Currently, a good correlation between specific features of the imaginary impedance spectrum and the progress of the reaction has been found to hold under isothermal conditions. In this paper the correlation between the impedance and the progress of the reaction is extended to dynamic cure conditions. Impedance flow monitoring of the filling stage of liquid moulding of glass composites, based on lineal sensors, has been developed and reported recently. Here, this technique is extended to the case of conductive reinforcements with the development of a new sensing system. The system performance is tested against visual observation of the flow front position during resin transfer moulding.